On thinking of Traditional Chinese Medicine nursing in Huangdi Neijing (从《黄帝内经》中论现代中医特色护理) - ZHANG Jing (张敬); TANG Ling (唐玲); ZHANG Dahua (张大华); ZHANG Xuejian (张雪键); LIU Jing (刘静); YANG Jinrui (杨金瑞) (Association of Integrative Nursing, 2023)
The classic representative work of Traditional Chinese Medicine, Huangdi Neijing, contains a profound connotation of Traditional Chinese medicine. It contributes to inspire the clinical thinking of Traditional Chinese medicine in the study of Huangdi Neijing, apply syndrome differentiation in conducting traditional Chinese medicine technology and nursing methods, and improve the quality of Traditional Chinese Medicine nursing. This paper briefly discussed the impact of Huangdi Neijing on Traditional Chinese Medicine nursing in modern time, and provided reference for development of Traditional Chinese Medicine nursing. (《黄帝内经》蕴育着深厚的中医内涵, 通过研读《黄帝内经》, 有助于启发中医临床思维, 辨证应用中医技术及护理方法, 提升中医护理质量。本文就《黄帝内经》对现代中医特色护理的影响进行简要阐述, 以期为现代中医护理学的发展提供更多理论依据。)